INFLUENCE DEVELOPMENT CAREER AND PROMOTION POSITION ON EMPLOYEE PERFORMANCE - Ramadina, Savela Arthamevia; Cikusin, Yaqub; Krisdianto, Dadang (International Journal of Entrepreneur and Business Administration, 2023)
The aim of this research is to see how the performance of employees at the Tirta Umbulan Pasuruan Regional Drinking Water Company is influenced by career development and job promotions. Quantitative research design involves observation and questionnaire strategies. Research participants are people​​​​​ Tirta Umbulan Regional Public Drinking Water Company . Saturated sampling used in this research with a total of 60 respondents. Research findings show that Employee Performance (Y) is partially influenced by the variables Career Development (X1) and Position Promotion (X2). Based on the findings of the F test, it is known that Fcount > Ftable (11.348 > 3.16 ) and the value is significant (0.00 < 0.05), so that career development and job promotion can have a simultaneous impact on employee performance. The coefficient of determination test states that career development and job promotions have an impact on employee performance by 28.5 %. The remaining 71.5% is influenced by other variables outside this equation or variables that are not researched.